Rice Crop Manager - Philippines - CGIAR Research Program on Rice (2021)
More than 1.7M recommendations generated for farmers. Monitoring for dry season of 2018 results: 27% of respondents have taken up recommended practices from RCM and benefit by 640 kg additional yield and 210 USD added net return/ha/season more than those who have not taken up the recommended practices.